Relação com o saber matemático de alunos em risco de fracasso escolar - Simone Amorim Castro Kiefer Oliveira (2009)
In this work we report a study on the relation with knowledge (Charlot) of a specific group of eighth grade students of two different schools. This group (the K group) is composed by students at risk of failure in mathematics. Our objective was to understand the relation with knowledge of the students of the K group, as compared to the relation with knowledge of the students of another group (the R group) in the same classroom, this last one being composed by students with a history of success in school mathematics. Data were collected using interviews with the students and their families and written questionnaires. Results point to significant differences between these two groups, not only in their performance in school mathematics, but in all of the six aspects of relation with knowledge encompassed by our study.